The effect of public ownership, risk management committee, bank size, leverage, and board of commissioners on risk management disclosures (empirical study in banking sector companies listed on the Indonesia stock exchange for the period 2011-2015) - Nisa Nailur Rahma; Luciana Spica Almilia (STIE Perbanas Surabaya, 2018)
Every company is defi nitely at fi nancial risk or operational risk. In a uncertain econimic situation, risk management is one of the ways to reduce and deal with the possible risk faced by the company. This research aims to analyze the effect of public ownership, risk management committee, bank size, leverage and the board of commissioners on the disclosure of risk management. The population used in this study is secondary data derived from annual reports of conventional banking companies listed on the Indonesia Stock Exchange (IDX), period 2011-2015. A sample of 35 companies is obtained through purposive sampling method. The statistical method used is regression analysis. Hypothesis test is conducted by t test and F test. The results of this study show that (1) public ownership has no effect on risk management disclosure, (2) risk management committe has an effect on risk management discolsure, (3) bank size has no effect on risk management disclosure, (4) leverage has an effect disclosure risk management, (5) the board of commissioners has an effect on risk management disclosure.